Decrease in C-reactive protein level by atorvastatin treatment in population with coronary artery disease - Karaca, I; Akbulut, M; Kilicoglu, AE; Ilkay, E; Pekdemir, M; Ozbay, Y; Arslan, N (Medimond S R L, 2001)
High course of CRP which is inflammation markers in population, with coronary artery disease is regarded as an indicator of poor prognosis. Previous findings demonstrate that direct inflammatory effect in endothelial level may increase CRP. Purpose of the study was to evaluate anti inflammatory effect of 20 mg atorvastatin in population with coronary artery disease by leacking of its effect on CRP. Group A (n=46): 20 mg/day atorvastatin was given in addition to classic antianginal treatment. Group B (n=32): Classic antianginal treatment was given. Following 4 week treatment some measurements were repeated. As a result in Group A, beginning CRP value decreased from 20.3 (% 95 CI, 9-31.8) to 10.8 (% 95 CI, 2.7-18.9) (p<0.001). In Group B CRP value decreased from 17 (% 95 CI, 13.1-21) to 12.77 (% 95 CI, 9.7-15.9) (p<0.01). Decrease in group A was more than in group B (p=0.003).
4th International Congress on Coronary Artery Disease -- OCT 21-24, 2001 -- PRAGUE, CZECH REPUBLIC
Keywords: Average Cholesterol Levels; Unstable Angina; Inflammation; Pravastatin; Events; Risk; Men